Lethal toxicity of monocrotophos on the juveniles of rohu and mrigal - Sulekha, B T; Anna Mercy, T V; Nair, J R (Indian Journal of Fisheries, 2011)
The 96 hour LC50 value of monocrotophos - a widely used organophosphate pesticide in the paddy fields of Kerala on the juveniles of rohu and mrigal are found to be 46.34 and 42.33 ppm respectively. It is seen that rohu is more resistant than mrigal. Both rohu and mrigal can be recommended as potential candidates for culture practices in the paddy-cum-fish culture systems, as they show high pesticide tolerance. But further studies are required on the residue accumulation and depuration in the body of these fishes